Betsy Ross and the making of America - Miller, Marla R. (New York : Henry Holt, 2010)
A richly woven biography of the beloved patriot Betsy Ross, her fabled creation of "the first flag," and an enthralling portrait of everyday life in Revolutionary War-era Philadelphia.
Six hundred miles nearer the sun. The light within ; A nursery to the Lord ; Pins and needles ; Crafting comfort -- The furnace of affliction. Combustible matters ; Domestic rebellions ; Union and disunion ; Mr. and Mrs. Ross ; Meditations in trouble -- True colors. Crafting colors ; Signals of independence ; The mariner's bride ; The occupied city ; Privateer to prisoner -- Peace and prosperity. Third time's a charm ; For Lord and empire ; Brotherly love ; Fever ; The federal edifice -- Endings and beginnings. War, redux ; A port in the storm.
Includes bibliographical references and index.
Keywords: Ross, Betsy, -- 1752-1836.; Revolutionaries -- United States -- Biography; Flags -- United States -- History; Philadelphia (Pa.) -- History -- Revolution, 1775-1783.; Amerikaanse Vrijheidsoorlog; Vlaggen; Vaderlandsliefde; Philadelphia (Verenigde Staten)